EFL Textbook Evaluation: The Analysis of Tasks Presented in English Textbook - Mutiara Ayu; Rita Inderawati (Universitas Teknokrat Indonesia, 2019)
The use of English textbook does not only become a guide to the teachers when delivering the materials, but also presents necessary input through various explanations and activities. On the side of the learners, it also influences their attitudes and performance to the materials. This phenomenon challenges the writer to conduct research-based article concerning textbook evaluation to analyze the tasks and the distribution (simple to complex) of tasks presented in English textbook used in senior high school. The findings show that the English textbook entitled Bahasa Inggris SMA/MA/SMK/MAK Kelas X Semester 1 has interesting tasks which meet the objectives in curriculum 2013 and a good distribution of tasks across chapters and the whole book.